RINOMETRIA ACÚSTICA E SEPTOPLASTIA: AVALIAÇÃO PRÉ E PÓS-OPERATÓRIA - Soares, Vera Sofia; Costa, Sandra; Neves, José Carlos; Amorim, A. Margarida; Paiva, Sofia; Gapo, Carla; Ribeiro, João Carlos; Romão, José; Tomé, Pedro; Cruz, Mário; et al. (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2005)
.